PENGEMBANGAN E-MODUL DENGAN MENGGUNAKAN APLIKASI FLIP BUILDER BERBASIS PROBLEM SOLVING MATA KULIAH PERPAJAKAN PRODI PENDIDIKAN EKONOMI UNIMED - Septiana G.A.N; Roza Thohiri (FKIP Unswagati, 2022)
AbstractThis research aims to develop an E-module using a Flip Builder Application Based on Problem Solving in the subject of Taxation for PPH Chapter 23,24,25, 26, and Chapter 28(a)/29. This research was conducted using the Research and Development (R&D) method. The research and development steps are guided by the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The development stage has 3 stages, namely 1). Validation test in which there are two validators, namely material experts and media experts. 2). The practicality test is a test from a tax lecturer (one person). 3). The next step is to test the attractiveness of the E-module, namely the individual test (3 people) and the small group test (6 people). limited group trial by distributing online questionnaires. The validation results from material experts and media experts obtained that the criteria could be used with partial revisions results is 85%Â and could be used with partial revisions with 84% results. The results obtained from the practicality test in which the course lecturers amounted to 91.7% and individual trials and small group trials of 93%.Keywords : E-modul, Flip Builder, Problem Solving